Crotalaria Sowing Times Intercropped with Off-Season Maize in the Variability of Soil Temperature and Moisture - Daniel, Diego Fernando; Dallacort, Rivanildo; Barbieri, João Danilo; Modolo, Alcir José; Carvalho, Marco Antonio Camillo de; Tieppo, Rafael Cesar; Yamashita, Oscar Mitsuo (Journal of Agricultural Studies, 2022)
The thermal regime and the dynamics of soil moisture affect crop yield. Therefore, there is a need to understand the extent to which the intercropping system modifies the variability of soil temperature and moisture conditions for optimal growth and yield of the maize crop. This study aimed to evaluate the influence of different sowing times of crotalaria in an intercropping system with irrigated and non-irrigated off-season maize in the variability of soil temperature and moisture. The experiment consisted of twelve treatments, consisting of different cropping systems (intercropping): maize in a single crop (MS); sowing of crotalaria simultaneous with maize (MCS); sowing of crotalaria with maize in the VE stage (MCVE); sowing of crotalaria with maize in stage V2 (MCV2); sowing of crotalaria with maize in stage V4 (MCV4); sowing of crotalaria with maize in stage V6 (MCV6), in irrigated and non-irrigated systems. Soil temperature was monitored at depths of 10, 20, 30 and 40 cm, and soil moisture was monitored at a depth of 20 cm using "K-type" thermocouple sensors and time domain reflectometry (TDR) probes, which were all connected to a Datalogger and programmed to store the collected data at 15-minute intervals. Irrigation was carried out with a uniformity coefficient greater than 80% and a water depth of 10.38 mm h-1 with a sprinkler system. The intercropping of maize with crotalaria provides the soil with a smaller range of soil temperature, with higher values in the system without irrigation compared to the irrigated system. Soil moisture was lower in the single maize treatment, as it increased soil water evaporation compared to the intercropping treatments. In the irrigated system, the soil moisture was higher at 0.010 m3 m-3 in relation to the system without irrigation. The irrigated system obtained better results for maize yield than the non-irrigated system.